Import of Agricultural Products in the Intra-Regional Comprehensive Economic Partnership (RCEP) - Simanullang, Endang Sari; Dedi Budiman Hakim; Yusman Syaukat; Widyastutik (HABITAT, 2022)
The flow of agricultural products through imports has the potential to increase with the geographical conditions of adjacent RCEP countries. Economic and non-economic factors can affect imports of agricultural products. This study aims to analyze the spatial effect and the factors that influence the import of agricultural products in Intra RCEP. This study uses a data period from 2013-2019. The analytical method used in this research is Moran's global index, Local Indicator of Spatial Autocorrelation (LISA), and Geographically Weighted Panel Regression (GWPR). The results show a spatial effect of imports of agricultural products in intra-RCEP. China, Japan, and South Korea are countries that are geographically concentrated in importing agricultural products within the intra-RCEP. The factors that significantly affect the total value of imports of agricultural products are GDP per capita, trade openness, Foreign Direct Investment (FDI), and government effectiveness. The policy recommendations in this study are implementing the RCEP agreement in the long term, open market access, encouraging increased investment in the agricultural sector, and an efficient bureaucracy.